Site Soil Classification Interpretation Based on Standard Penetration Test and Shear Wave Velocity Data - Windu Partono; Muhammad Asrurifak; Edy Tonnizam; Frida Kistiani; Undayani Cita Sari; Kukuh Cahya Adi Putra (Journal of Engineering and Technological Sciences, 2021)
Site soil classification provides vital information for predicting the soil amplification or the site factor. The site factor is important for calculating the surface spectral acceleration in the seismic design of buildings. Based on the Indonesian seismic code, site soil classification can be conducted by calculating the average standard penetration (N-SPT) resistance, the average shear wave velocity (VS) and the average undrained soil strength (Su) of the upper 30 m of a subsoil layer. Different results may be obtained at the same location when the site soil classification is predicted using N-SPT than when using VS data. The restriction of N-SPT values until a maximum of 60 compared to a VS maximum of 750 m/sec can produce different soil classes and will directly impact the calculation of the surface spectral acceleration. This paper describes the different results of site soil classification prediction calculated using the average N-SPT and the average VS, conducted at Semarang City, Indonesia. Site soil classification maps developed based on both datasets are also presented, to evaluate the different site soil classification distributions. Only soil classes SD and SE were observed using N-SPT maximum 60, whereas soil classes SC, SD and SE were observed using N-SPT maximum 120.